PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SD NEGERI 243/VI BUNGO TANJUNG - Wardani, Edi; Wulan, Laila Purwasari Ning (Sosio Akademika, 2025)
This study aims to evaluate the effectiveness of implementing differentiated learning strategies in improving the reading skills of fourth-grade students at SD Negeri 243/VI Bungo Tanjung. This study used a Classroom Action Research (CAR) approach conducted in two learning cycles. The research sample consisted of 12 fourth-grade students. Data was collected through tests, observations, interviews, and documentation. The results showed an increase in students' reading skills after the implementation of differentiated learning, with an increase in the average reading test score from 50% in the first cycle to 75% in the second cycle. In addition, the learning process became more interesting and increased students' learning motivation. Based on these findings, it can be concluded that differentiated learning strategies are effective in improving the reading skills of fourth-grade students at SD Negeri 243/VI Bungo Tanjung.